MEDIA PEMBELAJARAN AKSARA JAWA DENGAN TEKNIK AUGMENTED REALITY MENGGUNAKAN VUFORIA SDK - Andri Syafrianto; Avianto Aldi Nugroho (LPPM STMIK El Rahma Yogyakarta, 2019)
Javanese script is a priceless cultural heritage. The form of the script and the art of making it become a legacy that deserves to be preserved. Javanese script is used in various Javanese texts and several other languages around the narrative area. This script is better known as Hanacaraka or Carakan. However, over time the use of Javanese script began to decrease. Many people don't know Javanese script. One of the causes is the form of Javanese script which is more difficult to understand than Latin script so that the interest in learning is reduced. In today's technological development, learning media are beginning to use technology as a learning tool. This is to improve the quality and effectiveness of learning. One of the technologies that has been implemented is Augmented Reality. This technology is able to represent real objects into virtual objects in the form of images, video or audio. Learning Javanese script can use this technology to improve the effectiveness of learning. This Augmented Reality was created using Vuforia who later designed the application using Unity. With the creation of Javanese script learning media applications that implement Augmented Reality technology, it is easier to understand Javanese script. Especially understanding the form and pronunciation. So that the knowledge and use of Javanese script will continue to be preserved.